Challenges in Implementing Free Nutritious Meals Policy: A Case Study of State Junior High School 5 Cileunyi, Bandung Regency - yuliyawati, rahma; Samrotul Fuadah, Shafira; Setiawan, Deni; Sopiuridwan, Ripan (GoResearch - Research & Publishing House, 2024)
The Free Nutritious Meals Policy is a key initiative on the part of the central government to support the fulfillment of nutritional quality and education for students. The objective of this study is to assess the extent of the challenges encountered in implementing the Free Nutritious Meals (MBG) policy at State Junior High School 5 Cileunyi, Bandung Regency, employing the policy implementation model developed by Van Meter and Van Horn. The present study employs a case study method with a descriptive qualitative approach, utilizing interviews, participatory observation, and document analysis as primary data sources from various stakeholders, including the school principal, teachers, students, and parents. The findings of this study suggest that the implementation of the Free Nutritious Meals policy is confronted with numerous challenges, including the absence of technical guidelines, inadequate human resources, and inadequate coordination among institutions. Teachers are performing an increasing number of tasks without adequate training, and their high workloads are beginning to affect the quality of the teaching and learning process. The exchange of information among institutions is characterized by inefficiency and a tendency towards unilateral communication. Despite the optimistic outlook of the implementers, the operational pressures they face have the potential to diminish their long-term motivation. The Free Nutritious Meals policy has been shown to have positive effects on student attendance and breakfast habits; however, its impact on family spending remains to be seen. The findings of this study suggest the necessity for enhancements in the implementation system, augmented communication, training for implementers, and routine evaluations to ensure the policy operates at its optimal capacity. This study underscores the importance of local adaptation in the implementation of public policies based on real needs.